2020
DOI: 10.1177/1938640020980911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Subtalar Arthroereisis for Management of Planovalgus Foot in Children With Cerebral Palsy: 3-Year Follow-up

Abstract: Background Planovalgus deformity of the foot is common among cerebral palsy (CP) patients. It is an upcoming topic with debate and controversy that require further studies. Many clinical studies involving arthroereisis have shown acceptable results in short- and mid-term follow-up. The aim of this work was to evaluate the outcome of arthroereisis using a conventional screw placed percutaneously across the talocalcaneal articulation for the treatment of moderate planovalgus deformity in children with CP. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…Thirty-seven percent of our study group underwent simultaneous Achilles tendon lengthening. Other authors also reported performing additional procedures in 17-100% of patients undergoing arthroereisis [1,3,7,[9][10][11][12][13][14][16][17][18]. Those additional procedures had no effect on either clinical or radiological outcomes [10,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-seven percent of our study group underwent simultaneous Achilles tendon lengthening. Other authors also reported performing additional procedures in 17-100% of patients undergoing arthroereisis [1,3,7,[9][10][11][12][13][14][16][17][18]. Those additional procedures had no effect on either clinical or radiological outcomes [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…Arthroereisis, which is used in the treatment of symptomatic pes planovalgus, is minimally invasive, inexpensive, produces few complications, and ensures high rates of patient satisfaction [1,2,[4][5][6][7][8][9]15,17,19]. The implants used for arthroereisis mechanically limit foot pronation and improve proprioception, which helps achieve the correction of pes planovalgus deformity [1][2][3]5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…]. Arthroereisis has had a recent resurgence in the literature [41][42][43][44][45]. However, most neuromuscular pediatric orthopedic surgeons have tended to avoid this technique due to high complication rates and less correction capacity than other techniques [46].…”
Section: Andandmentioning
confidence: 99%